Decarcerating America: from mass punishment to public health - Drucker, Ernest M. (The New Press, 2018)
Ending mass incarceration : six bold reforms to rapidly reduce incarceration without compromising public safety / Natasha A. Frost, Todd R. Clear, and Carlos E. Monteiro -- Better by half : the New York City story of winning large-scale decarceration while increasing public safety / Judith A. Green and Vincent Schiraldi -- Lessons from California on prison and jail downsizing / Michael Romano -- The role of judges in ending mass incarceration / Judge Robert Sweet and James Thompson -- Public defense and decarceration : advocacy on the front lines / Robin Steinberg, Skylar Albertson, and Rachel Maremont -- Making drug policy reform work for meaningful decarceration / Gabriel Sayegh -- Transforming our responses to violence / Danielle Sered -- Minimizing the impact of parental incarceration / Elizabeth Gaynes and Tanya Krupat -- Health and decarceration / Ross MacDonald and Homer Venters -- Release aging people in prison : a sound policy initiative necessary for meaningful decarceration / Mujahid Farid and Laura Whitehorn -- Health care as a vehicle for decarceration / Daliah Heller -- Come close in : voices of survivors of mass incarceration / Kathy Boudin -- Dealing with drug use after prison : harm reduction therapy / Jeannie Little, Jenifer Talley, Scott Kellogg, Maurice Byrd, and Sheila Vakharia -- Prisons to ploughshares : new economies for prison towns / Eric Lotke